Diabetes treatments and risk of heart failure, cardiovascular disease and all-cause mortality: cohort study in primary care - Hippisley-Cox, Julia; Coupland, Carol (BMJ Publishing Group, 2016)
Objective: To assess associations between risks of cardiovascular disease, heart failure, and all cause mortality and different diabetes drugs in people with type 2 diabetes, particularly newer agents, including gliptins and thiazolidinediones (glitazones).